PERSEPSI PENGUNJUNG TERHADAP KEBERADAAN KEBUN RAYA BANUA DI KOTA BANJARBARU KALIMANTAN SELATAN - Dewi Permatasari; Khairun Nisa; Abdi Fithria (Universitas Lambung Mangkurat, 2020)
The purpose of this study was to find out the characteristics of visitors to the Banua Botanical Gardens, to find out the motivations of visitors who came to the Banua Botanical Garden and to study visitors' perceptions of the existence of the Banua Botanical Garden in Banjarbaru City. The method used in this research is descriptive survey with qualitative and quantitative approaches. Data is collected through observation and interviews. The results of the study showed that the characteristics of visitors who came to Banua Botanical Garden were classified by sex, specifically 50% male and 50% female, the age of visitors ranged from 11 years to 50 years and the education of visitors was mostly students. Motivation of visitors based on the reasons for visiting the Banua Botanical Garden is dominated by visitors who have a reason to visit 75% of the panorama of city forests, to see arts and culture as much as 4%, to see flora and fauna as much as 6% and others 15%. Community acceptance of the existence of the Banua Botanical Garden is very good according to 37% of visitors, good 51% and moderate 12%.Keyword: Visitors' perception; Banua Botanical Garden